Bevacizumab for newly diagnosed pleural mesothelioma in the Mesothelioma Avastin Cisplatin Pemetrexed Study (MAPS): a randomised, controlled, open-label, phase 3 trial. Issue 10026 (2nd April 2016) - Zalcman, Gérard; Mazieres, Julien; Margery, Jacques; Greillier, Laurent; Audigier-Valette, Clarisse; Moro-Sibilot, Denis; Molinier, Olivier; Corre, Romain; Monnet, Isabelle; Gounant, Valérie; Rivière, Frédéric; Janicot, Henri; et al.
Summary: Background: Malignant pleural mesothelioma is an aggressive cancer with poor prognosis, linked to occupational asbestos exposure. Vascular endothelial growth factor is a key mitogen for malignant pleural mesothelioma cells, therefore targeting of vascular endothelial growth factor might prove effective. We aimed to assess the effect on survival of bevacizumab when added to the present standard of care, cisplatin plus pemetrexed, as first-line treatment of advanced malignant pleural mesothelioma. Methods: In this randomised, controlled, open-label, phase 3 trial, we recruited patients aged 18–75 years with unresectable malignant pleural mesothelioma who had not received previous chemotherapy, had an Eastern Cooperative Oncology Group performance status of 0–2, had no substantial cardiovascular comorbidity, were not amenable to curative surgery, had at least one evaluable (pleural effusion) or measurable (pleural tumour solid thickening) lesion with CT, and a life expectancy of >12 weeks from 73 hospitals in France. Exclusion criteria were presence of central nervous system metastases, use of antiaggregant treatments (aspirin ≥325 mg per day, clopidogrel, ticlopidine, or dipyridamole), anti-vitamin K drugs at a curative dose, treatment with low-molecular-weight heparin at a curative dose, and treatment with non-steroidal anti-inflammatory drugs. We randomly allocated patients (1:1; minimisation method used [random factor of 0·8]; patients stratified by histology [epithelioid vs sarcomatoid or mixed histology subtypes], performance status score [0–1 vs 2], study centre, or smoking status [never smokers vs smokers]) to receive intravenously 500 mg/m 2 pemetrexed plus 75 mg/m 2 cisplatin with (PCB) or without (PC) 15 mg/kg bevacizumab in 21 day cycles for up to six cycles, until progression or toxic effects. The primary outcome was overall survival (OS) in the intention-to treat population. Treatment was open label. This IFCT-GFPC-0701 trial is registered withClinicalTrials.gov, numberNCT00651456 . Findings: From Feb 13, 2008, to Jan 5, 2014, we randomly assigned 448 patients to treatment (223 [50%] to PCB and 225 [50%] to PC). OS was significantly longer with PCB (median 18·8 months [95% CI 15·9–22·6]) than with PC (16·1 months [14·0–17·9]; hazard ratio 0·77 [0·62–0·95]; p=0·0167). Overall, 158 (71%) of 222 patients given PCB and 139 (62%) of 224 patients given PC had grade 3–4 adverse events. We noted more grade 3 or higher hypertension (51 [23%] of 222 vs 0) and thrombotic events (13 [6%] of 222 vs 2 [1%] of 224) with PCB than with PC. Interpretation: Addition of bevacizumab to pemetrexed plus cisplatin significantly improved OS in malignant pleural mesothelioma at the cost of expected manageable toxic effects, therefore it should be considered as a suitable treatment for the disease. Funding: Intergroupe Francophone de Cancérologie Thoracique (IFCT).